Clinical Evaluations of Fathers Based on Sexual Orientation and Gender Role Expression. Issue 3 (27th May 2019) - Miller, Deborah J.; Spengler, Paul M.
Abstract: Attention has recently been given to how traditional masculinity ideologies impact men's well-being in a variety of contexts. We sought to test the impact of masculinity ideology on counseling psychologists' evaluations of fathers who varied on sexual orientation (heterosexual or gay) and gender role expression (traditional or nontraditional masculinity). One hundred and thirty-three counseling psychologists were randomly assigned to evaluate one of four experimentally manipulated vignettes regarding an adoptive father in distress on measures of personal reactions, parenting skills, and adjustment. We hypothesized that counseling psychologists would give poorer ratings to fathers who violated traditional masculinity ideology in sexual orientation or gender role expression, with masculinity ideology as a moderator. MANCOVA analysis showed differences in the way participants evaluated fathers, but not in the ways we predicted based on gender role strain theory. A follow-up descriptive discriminant analysis revealed that gay fathers received more favorable therapist personal reactions, and gender nontraditional fathers were rated as having more favorable parenting skills and less favorable overall adjustment. In general, the participants' endorsement of masculinity ideology was low and had little variability which limited the scope of the moderation analysis. Findings are discussed in relation to masculinity and gender role studies.